Neutrino Detection Rates from Lepto-hadronic Model Simulations of Bright Blazar Flares - Joshua Robinson; Markus Böttcher (The Astrophysical Journal)
There is mounting evidence that blazars are the sources of part of the very-high-energy astrophysical neutrino flux detected by IceCube. In particular, there have been several spatial and temporal coincidences of individual IceCube neutrino events with flaring blazars, the most prominent of them being IceCube-170922A, coincident with a multiwavelength flare of TXS 0506+056. Motivated by this, we used the time-dependent lepto-hadronic code OneHaLe to model the spectral energy distributions and light curves of a sample of bright γ -ray flares of blazars detected by Fermi-Large Area Telescope, for which Kreter et al. provided calorimetric estimates of the expected neutrino detection rates. Flares were modeled with temporal changes of the proton injection spectra. Our analysis shows that the calorimetric approach overestimates the increase in neutrino production by a factor of typically ∼10 if the γ -ray emission is dominated by proton-synchrotron radiation.